Perancangan Sistem Informasi Persediaan Barang Pada PT. Pacific Paint Menggunakan PHP dan MySQL - Muhamad, Irpani; Hidayat, Wahyu; Handayani, Indri (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
In the era of development of information technology at this time, the use of computers at PT. Pacific Paint which is located at jl.bouraq lio baru no.33 rt.004 rw.001 batuceper city tangerang province banten post code 15122 is very important to support all information needs at PT. Pacific Paint, especially in inventory activities. The methodology used is a growth system of a life cycle approach starting from analyzing the running system and the final results achieved from the report, namely the formation of a system procedure and designing an inventory information system using php and mysql which is expected to improve operational performance of employees at PT. Pacific Paint so that the information obtained will be more effective and efficient.